The effect of emotion card games on emotional intelligence among elementary school-aged children: a quasi-experimental study in Mataram, Indonesia - Moh. Arip; Sri Susantini; Martha Meti Kodi; Melati Inayati Albayani; Novi Enis Rosuliana (International Journal of Public Health Science (IJPHS), 2026)
Emotional intelligence is a key skill influencing adaptation, communication, and personal growth in elementary school-aged children. Emotional card games offer a promising interactive approach to enhance children's emotional competencies. To analyze the effect of emotional card games on the emotional intelligence of elementary school-aged children. A quasi-experimental pretest-posttest control group design was conducted among 77 first-grade students at MI Mambaul Khair NW Bertais Mataram in 2025. The intervention group (n = 39) participated in three sessions of an emotional card game, while the control group (n = 38) received no intervention. Emotional intelligence was measured using a validated 24-item questionnaire. The intervention group demonstrated a significant increase in emotional intelligence scores from pre-test to post-test (p = 0.007), whereas the control group showed no significant change. Between-group comparison confirmed significantly higher post-test scores in the intervention group (p = 0.006). After adjusting for confounding variables and baseline scores, the intervention effect remained statistically significant (p < 0.001). Emotional card games effectively improve emotional intelligence among elementary school-aged children. These findings support the integration of game-based social-emotional learning strategies into elementary school curricula. School health practitioners and educators can utilize this low-cost, engaging intervention to promote children's emotional well-being and support holistic child health development.